Kualitas Semen Babi Landrace Dalam Pengencer Semen Sitrat-Kuning Telur Yang Ditambah Glukosa Dengan Konsentrasi Berbeda - Paskalius Leki Nahak; Agustinus A. Dethan; Kristoforus W. Kia (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2022)
The purpose of this study was to determine the effect of shelf life in Beltsville Thawing Solution (BTS) cement on motility, viability, abnormality and degree of storage (pH) of landrace pig semen. The semen used was fresh semen from a 4-year-old Landrace boar. This study used an experimental method using a completely randomized design (CRD) with four treatments (P0 10%, P1 10%, P2 10% and P3 10%) and four replications so that there were 16 experimental units. The results showed that the BTS cement diluent was significantly different (P>0.05) on the motility of spermatozoa with the average value of each treatment being P0 (68.25%), P1 (58.25%), P2 (38.50%). and P3 (10.75%). The percentage of spermatozoa viability was significantly different (P<0.05) between treatments, where the P2 treatment was relatively the same as the P3 and P4 treatments but was higher than the P1 treatment with respective values P1 (83%), P2 (90.1%) , P3 (93.5%) and P4 (91.5%). Percentage of spermatozoa abnormalities resulting from analysis of variance (ANOVA) from each treatment there was a non-significant difference (P>0.05) where the values were P1 (8.2%), P2 (9.2%), P3 (8.1%) and P4 (9.2%). The degree of relative difference (pH) was significant (P<0.05) between treatments, where the treatment was the same as P2 but more than P4 treatment. On the other hand, P3 was relatively the same as treatment P1, P2 and P4, with the respective treatments being P1 (8.36), P2 (7.99), P3 (7.676) and P4 (6.83). It can be said that the use of different glucose concentrations in the diluent of egg yolk citrate semen with good quality, namely in the P3 treatment with a glucose concentration of 15%, the average percentage of individual motility was 64%, the percentage of live spermatozoa was 93.5%, the percentage of abnormal spermatozoa was 8.1%. and the average pH (degree so) of cement is 7.68.